Prioritising health in anti-doping: What Australians think - Mazanov, J.; Huybers, T.; Connor, J. (Journal of Science and Medicine in Sport, 2012)
Objectives: There is debate concerning whether the guiding paradigm for anti-doping policy should be the current legalistic approach or a "harm minimisation" approach prioritising athlete health. This study sought to determine whether a representative sample of Australians prioritises health above other concerns using the World Anti-Doping Code`s Spirit of Sport statement which lists the 11 attributes that define the moral basis for anti-doping. Design: A Best-Worst Scaling (BWS) Balanced Incomplete Block Design experiment using 11 choice sets of five Spirit attributes from the set of 11, with the attributes within each choice set in a random order. Methods: A representative sample of n = 168 Australians responded to an on-line survey. The BWS scores defined the relative ranking of each attribute to define an aggregate model and demographically defined models (gender, education, sports participation and sports following). Results: Health was ranked as 7/11 in the aggregate model. Only those who did not follow sport prioritised health (2/11), with other demographic models failing to show a meaningful departure from the aggregate model. Conclusions: Australians ranked health below other attributes in the Spirit of Sport, appearing to prioritise "rule following" consistent with the legalistic approach. This challenges the harm minimisation approach to managing the role of drugs in sport and suggests that rule-following and legalistic approaches to drug use should take precedence over health messages.